ANALISIS MANAJEMEN PELAYANAN JAMAAH DALAM MENINGKATKAN KEPUASAN PADA PT. PENJURU WISATA NEGERI KOTA PADANG - Ramido Ramido; Khadijah Nurani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The background of this research is that the high interest of the Muslim community in wanting to go for Umrah indicates that the economy of the Muslim community is getting better, resulting in the emergence of many Umrah service companies everywhere. The implementation of Umrah Pilgrimage Service Management is the thing that pilgrims pay the most attention to, good service management is an important key to success in getting satisfaction for pilgrims and the wider community and can enhance a good corporate image.The research method used in this study is a qualitative approach, the type of research is field review and is descriptive in nature. Data collection methods used by the authors in this study are observation, documentation, and interviews. Sources of data from employees and members of the AET Travel Internasional office of PT. Padang City State Tourism Direction. The data analysis technique used is data reduction and data presentation and drawing conclusions. The results of the study show that service management for Umrah pilgrims in increasing congregation satisfaction is carried out by AET Travel Internasional PT. The direction of the Padang City State Tourism is to use service management indicators, namely polite behavior, delivery methods, delivery times, hospitality. In carrying out these services AET Travel Internasional PT. Padang City Tourism Direction puts forward indicators of service quality, namely reliability, assurance, tangible, empathy, responsiveness